Factors influencing bank officers into recommending financial products to SME’s: A literature review - Yong, Wooi Keong * (Universiti Teknologi Malaysia, 2019)
Previous literature indicates that there have been difficulties by small and medium sized enterprises as well as agricultural and mining sectors in securing funding from banks to develop their businesses. This paper aims to examine the basic determinants of bank officers intention to properly vet applicants of financial loans using the decomposed theory of planned behaviour (DTPB). It is concluded that the variables proposed in previous studies is sufficient to build the framework to study the intention to recommend financial products to SME’s.